PENGGUNAAN BEBERAPA JENIS PUPUK KOTORAN DOMBA DAN AYAM TERHADAP PERTUMBUHAN RUMPUT PAKCONG (Pennisetum Purpureum Cv Thailand) - Muhammad Hasan; Meriksa Sembiring (Jurnal Cakrawala Ilmiah, 2024)
The aim of the research was to determine the effect of using manure from sheep manure and chicken manure on the growth of Pakchong Grass. The data analysis method used in this research was a non-factorial completely randomized design (CRD) consisting of 4 treatments and 5 replications, namely P0 (without manure), P1 (25% sheep manure + 75% chicken manure), P2 (fertilizer sheep pen 50% + chicken manure 50%) and P3 (sheep manure 75% + chicken manure 25%). The parameters observed in this research were the number of tillers, plant height, and fresh material production. The results showed that treatment P1 was the best treatment in terms of fresh material production, plant height and number of tillers. the use of a combination of sheep and chicken manure on the growth of pakcong grass (Pennisetum Purpureum Cv Thailand) with the number of Pennisetum purpureum cv seedlings. Mott grass 4.88, plant height 175 cm, and fresh material production 18.30 kg/plot